Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Disiplin Kerja Pegawai Negeri Sipil Pada Sekretariat Kota Administrasi Jakarta Selatan Tahun 2023 - Cahyani, Melianawati; Susetyo, Ivan Budi (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The lack of discipline among employees at the Secretariat of South Jakarta City Administration has become an issue that requires attention as it can impact the performance of civil servants, ultimately affecting the quality and quantity of government services. This issue is attributed to factors such as slow task completion, leadership style, and motivation. The aim of this research is to utilize the research problem formulation to identify, assess, and analyze the influence of leadership style and work motivation on the discipline of employees at the Secretariat of South Jakarta City Administration. This study is descriptive quantitative research, conducted on a population of 130 employees at the Secretariat of South Jakarta City Administration in the year 2023, with a sample size of 65 individuals (50% of the population). Data was collected through the distribution of questionnaires to respondents and analyzed using multiple regression analysis in SPSS version 25. From the results of the research and analysis, it can be concluded that leadership style partially contributes to 65,2% of employee discipline at the Secretariat of South Jakarta City Administration, work motivation contributes 42,8%, and when considered simultaneously, leadership style and work motivation together contribute 67,2% to employee discipline, with the remaining 32,8% influenced by other factors not included in this study.